Impact of Trump's Price Policy on the TTIP Negotiation Process between the United States and the EU - Dika Novitasari; Devita Prinanda (Budapest International Research and Critics University, 2022)
This study aims to analyze and describe the impact of Trump's tariff policy on the TTIP negotiation process between the United States and the European Union. The method used in this study is to search for accredited journals through the help of hazing software and use Mendeley software to determine the research gap clusters to assist the author in analyzing how Trump's tariff policy influences the TTIP negotiation process. One form of the main focus that is often discussed in the negotiation process at the TTIP until the 15th round is tariff relief, tariff, non-tariff barriers, and FDI barriers. The European Union has high hopes through the implementation of the TTIP from the negotiation process that had previously been in operation under the Barack Obama administration for three years and could be continued by the President of the United States in the next period until the TTIP was implemented into a form of Trade and Investment Partnership cooperation that could have a significant influence on the welfare of the European Union's GDP, Wages, export and import tariffs. Findings in this study With the inauguration of Donald Trump as President of America in 2017 and strongly through Trump's Tariff policy, it made sense of pessimism for the European Union to continue the negotiation process on the TTIP so that in 2019, the Council of the European Union issued a decision on article 3 through COUNCIL DECISION (EU) 2019 which reads that